Rethinking Gamification - Fuchs, Mathias; Fizek, Sonia; Ruffino, Paolo; Schrape, Niklas (meson press, 2014)
Gamification marks a major change to everyday life. It describes the permeation of economic, political, and social contexts by game-elements such as awards, rule structures, and interfaces that are inspired by video games. Sometimes the term is reduced to the implementation of points, badges, and leaderboards as incentives and motivations to be productive. Sometimes it is envisioned as a universal remedy to deeply transform society toward more humane and playful ends. Despite its use by corporations to manage brand communities and personnel, however, gamification is more than just a marketing buzzword. States are beginning to use it as a new tool for governing populations more effectively. It promises to fix what is wrong with reality by making every single one of us fitter, happier, and healthier. Indeed, it seems like all of society is up for being transformed into one massive game. The contributions in this book offer a candid assessment of the gamification hype. They trace back the historical roots of the phenomenon and explore novel design practices and methods. They critically discuss its social implications and even present artistic tactics for resistance. It is time to rethink gamification!